Health-promoting schools in Taiwan: School principals' and teachers' perspectives on implementation and sustainability. (March 2019) - Liu, Chieh-Hsing; Chang, Fong-Ching; Liao, Li-Ling; Niu, Yu-Zhen; Cheng, Chi-Chia; Shih, Shu-Fang
Objective: This study assessed school principals' understanding, attitudes and willingness to influence the implementation of the health-promoting schools (HPS) programme in Taiwan and teachers' willingness to sustain it. Method: In 2014, a total of 1, 140 school principals and 1, 110 teachers (HPS coordinators) completed questionnaires concerning their perspectives on implementation and sustainability. Results: Compared with teachers, school principals reported higher levels of willingness to sustain HPS implementation. School principals' levels of understanding of HPS and willingness to sustain it were significantly associated with higher levels of HPS implementation and an increase in teachers' willingness to sustain HPS implementation. Conclusion: School principals' understanding and willingness to support are central to the effective implementation and sustainability of initiatives such as HPS.